Study of the Atopic March: Development of Atopic Comorbidities. Issue 4 (7th June 2016) - Schneider, Lynda; Hanifin, Jon; Boguniewicz, Mark; Eichenfield, Lawrence F.; Spergel, Jonathan M.; Dakovic, Rada; Paller, Amy S.
Abstract: Background: Atopic dermatitis (AD) is often the first step in the atopic march leading to the development of asthma or allergic rhinitis. The goal of this study was to determine whether early intervention with pimecrolimus limits the atopic march in infants with AD and to evaluate its efficacy and safety. Methods: This was a 3‐year double‐blind study in which patients were randomized to pimecrolimus or vehicle and then open‐label pimecrolimus for a planned further 3 years. Rescue topical corticosteroid was permitted if 3 days of study medication led to no improvement; investigators made decisions on rescue medication until week 14 and caregivers thereafter. Efficacy assessments included disease‐free days, Eczema Area and Severity Index, and body surface area affected. Results: Infants ages 3 to 18 months with recent‐onset AD (≤3 months) were observed for a mean of 2.8 years ( N = 1, 091). No significant differences between pimecrolimus‐ and placebo‐treated groups were found in the percentage of patients with AD who developed asthma (10.7%) or other allergic conditions (allergic rhinitis, 22.4%; food allergy, 15.9%; allergic conjunctivitis, 14.1%; one or more atopic comorbidities, 37.0%) by study end. Allergic rhinitis, food allergy, and having one or more atopic comorbidities (but not asthma or allergic conjunctivitis alone) developed significantly more often in infants with greater AD severity at baseline. Pimecrolimus was significantly more effective than vehicle for AD treatment at week 14. Adverse event incidences were similar. Conclusions: This longitudinal observation of infants with AD provides evidence of the atopic march. Pimecrolimus was safe and effective in infants with mild to moderate AD.